THE DEVELOPMENT OF STUDENT WORKSHEET WITH INDUCTIVE STRATEGY ORIENTED ON ACID BASE MATERIAL TO IMPROVE STUDENT CRITICAL THINKING SKILL (Universitas Negeri Surabaya, 2017)
This study was aimed to know the feasibility of student worksheet with inductive strategy oriented on acid base material to train student critical thinking skill. The feasibility was viewed acoording to theoretical and empirical feasibility. The empirical feasibility based on student response after using student worksheet with inductive strategy oriented on acid-base material developed. Theoretical feasibility is reviewed from the validation results. This research uses 4-D method, but only done until development stage (develop). Validation results shows percentage of content criteria is 83.33%, presenting criteria is 77.49% and 83.33% for language criteria. The results of student responses, the feasibility of student worksheet based on content criteria is 92.85%, 85% for presenting criteria and 97.5% for language criteria. Based on student responses and validation results can be conclude that student worksheet was very appropriate. Keywords: students’ worksheet, inductive strategy, critical thinking skill, acid base.